Exploring Parthenium weed biotypes by chloroplast DNA barcode analysis - Anjum,Tehmina (2020)
Abstract Background: Parthenium weed (Parthenium hysterophorus L.) is an invasive weed that has invaded vast regions of Pakistan in a relatively very short period of a decade or two, threatening the crop fields of the agrarian fed country. Parthenium hysterophorus L. is native of central South America and Gulf of Mexico, has now turned out to be a weed of global significance due to its alarming invasions and profuse spread in approximately all parts of the world. Its invasion is probably due to the contamination of its seeds in the imported grains from other countries of the world. Objective: During comprehensive sampling from Pakistan and Australia, it was observed that parthenium weed accessions exhibited several distinct morphological features present at different geographical regions. Therefore this study focuses on the use of plastid DNA barcodes (psbA-trnH) to evaluate the extent of variations in nucleotide sequences between the parthenium weed sampled accessions. Methods: The variability or genetic diversity was evaluated through sequencing of the amplified products and data was subjected to phylogenetic analysis in Molecular Evolutionary Genetic Analysis (MEGA; version 6.06) software. Results: In Maximum Likelihood tree, mainly two clades with three subdivisions are evident which showed increased heterogenity. The results of sequence based markers showed 12 haplotypes of P.hysterophorus populations (having two parsimony informative sites) with 10 indels and a few SNPs (single nucleotide polymorphisms). Conclusions: The results advocate that there have been multiple introductions of parthenium weed into Pakistan.